2018
DOI: 10.3390/geosciences8070245
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Hydrothermal Alteration: A Review of Methods

Abstract: Hydrothermal alteration is proximal to many base and precious metal deposits, and its products can provide insights into the characteristics of hydrothermal systems. To be useful to exploration geologists and researchers, however, alteration needs to be typified and quantified. Alteration type informs on mineralising style (e.g., have we found a porphyry or a volcanogenic massive sulphide deposit?), while quantification of its intensity helps position a sample within the system (e.g., how close are we to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 64 publications
2
44
0
2
Order By: Relevance
“…The global mass changes, as estimated by the modelled precursor method [45], point to mass gain being most pronounced for sample MS17-14 (Table 5). Individual mass changes within ±1 g (and ±10 g for SiO 2 ) per 100 g of precursor fall within the method's error and are considered negligible [47]. The volcanic rocks gained Fe and Mg and lost Ca (Table 5).…”
Section: Results Of the Quantification Of Hydrothermal Alterationmentioning
confidence: 73%
See 4 more Smart Citations
“…The global mass changes, as estimated by the modelled precursor method [45], point to mass gain being most pronounced for sample MS17-14 (Table 5). Individual mass changes within ±1 g (and ±10 g for SiO 2 ) per 100 g of precursor fall within the method's error and are considered negligible [47]. The volcanic rocks gained Fe and Mg and lost Ca (Table 5).…”
Section: Results Of the Quantification Of Hydrothermal Alterationmentioning
confidence: 73%
“…These authors suggested that increasing degrees of diffusion during an oxy-exsolution process form the following progression of textures: (1) trellis-type texture (thin ilmenite lamellae in all sets of {111} planes); (2) sandwich-type texture (thick ilmenite lamellae in one set of {111} planes); (3) granular ilmenite inside magnetite; and (4) external granular ilmenite. In the studied rocks, trellis-type texture is only observed in the Fe-Ti-oxides of volcanic rocks (Figure 7f 57 Fe, 24 Mg, 28 Si, 27 Al, 47 Ti, 51 V, and 52 Cr in the minerals of sample MS17-37. Mineral abbreviations are as reported in the literature [34].…”
Section: Magnetite Texturementioning
confidence: 92%
See 3 more Smart Citations